Stereoselective Thermal Isomerization of Bis(spiropyrazolone)cyclopropanes into (4Z)-4-[(Pyrazol-4-yl)methylene]pyrazolones - Dorofeeva, Evgeniya O.; Elinson, Michail N.; Vereshchagin, Anatoly N.; Nigmatov, Albert G.; Bushmarinov, Ivan S.; Nikishin, Gennady I. (Synlett, 2013)
Thermal isomerization of bis(spiropyrazolone)cyclopropanes in DMSO at 100 °C results in highly efficient formation of the corresponding 4-[(pyrazol-4-yl)methylene]pyrazolones in 90–98% yields after only five minutes. NMR and single-crystal X-ray diffraction analysis indicate stereoselective formation of the Z-isomers.
Keywords: isomerization; ring opening; spiro compounds; cyclopropane; pyrazolone